PENGGUNAAN ANTIDIABETIK ORAL PADA PASIEN DIABETES MELITUS TIPE II DI INSTALASI FARMASI RUMAH SAKIT PINNA BEKASI - Aries Meryta; Fachdiana Fidia; Alfina Swity (Jurnal Farmasi IKIFA, 2023)
The availability of oral antidiabetic drugs is very necessary because diabetic patients need these drugs for continuity. Thus, the management of pharmaceutical preparations and health supplies in hospitals is expected to run well and complement each other so that the necessary health supplies are always available whenever needed in sufficient quantities and guaranteed quality. The study aims to identify the incidence of oral antidiabetes in type II diabetes patients at the July-December pinna hospital pharmacy installation, 2021. The research is using a descriptive method using a total sampling retrieval technique. The data release is based on the entire prescription sheet containing the anti-diabetic 'diabetes which is 499' prescription sheet. According to the research, he found 19,464 anti-diabetic tablets. Based on the group of active medicine and substances most used is the biguanid (metformin) group of 13,356 tablets (68.62%), the 3rd generation sulfonilurea (glimepiride) group of 3,232 tablets (16.61%), the 2nd generation sulfonilurea (glibenclamid), 2,716 tablets (1395%), the alfa glukosidase (acarbose), 160 tablets (0.82%).